Co-pigmentation of black chokeberry (Aronia melanocarpa) anthocyanins with phenolic co-pigments and herbal extracts. (1st May 2019) - Klisurova, Daniela; Petrova, Ivalina; Ognyanov, Manol; Georgiev, Yordan; Kratchanova, Maria; Denev, Petko
Highlights: Co-pigmentation of aronia anthocyanins with 10 phenolic co-pigments was studied. The highest effect was with rosmarinic acid, syringic acid, catechin and chlorogenic acid. The effect was most profound at high co-pigment/pigment ratios not achievable in plants. Herbal extracts, in low concentrations were better co-pigments than pure compounds. Results could be applied for the development of aronia foods with improved color. Abstract: The co-pigmentation of black chokeberry ( Aronia melanocarpa ) anthocyanins with ten phenolic co-pigments was studied. Tested compounds provoked different co-pigmentation effect, manifested by hyperchromic and batochromic shifts. The co-pigmentation was accompanied by a magnification of color intensity and decrease of color hue, both related to a more pleasant color. The hyperchromic effect was the most significant for rosmarinic acid (51.02%), syringic acid (43.24%) and catechin (39.73%). However, it was observed at the highest pigment/co-pigment ratio (1:50), not achievable in plant matter. Targeting the potential practical application of co-pigmentation, we tested eight herbal extracts for their co-pigmentation ability with aronia anthocyanins. The use of herbal extracts led to a significant hyperchromic effect at much lower pigment/co-pigment ratios, compared to pure compounds. The use of selected herbal extracts as co-pigments opens realistic prospects for development of aronia functional foods with improved sensory properties and biological effects, due to enhanced color and anthocyanin stability.